2021
DOI: 10.3390/aerospace8110332
|View full text |Cite
|
Sign up to set email alerts
|

Weather Variability Induced Uncertainty of Contrail Radiative Forcing

Abstract: Persistent contrails and contrail cirrus are estimated to have a larger impact on climate than all CO2 emissions from global aviation since the introduction of jet engines. However, the measure for this impact, the effective radiative forcing (ERF) or radiative forcing (RF), suffers from uncertainties that are much larger than those for CO2. Despite ongoing research, the so called level of scientific understanding has not improved since the 1999 IPCC Special Report on Aviation and the Global Atmosphere. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Between 2016 and 2019, we found the following: (i) the growth in total fuel consumption and CO 2 emissions (+3.13 % yr −1 ) outpaced the total flight distance (+3.05 % yr −1 ) due to the use of larger aircraft types (mean aircraft mass, +1.3 % yr −1 ) (Fig. S6); (ii) total NO x emissions grew by +4.5 % yr −1 , which is likely attributable to the higher combustion pressure and temperature in more fuel-efficient engines (Kyprianidis and Dahlquist, 2017; Freeman et al, 2018); (iii) the mean nvPM EI n increased by +0.5 % yr −1 ; and (iv) the contrail cirrus net RF showed significant inter-annual variability (up to ±19 % relative to the mean, ranging between 204 and 280 mW m −2 ), consistent with Wilhelm et al (2021), indicating a stronger dependence on meteorology than the total flight distance (Fig. S12).…”
Section: Multi-year Statisticssupporting
confidence: 56%
“…Between 2016 and 2019, we found the following: (i) the growth in total fuel consumption and CO 2 emissions (+3.13 % yr −1 ) outpaced the total flight distance (+3.05 % yr −1 ) due to the use of larger aircraft types (mean aircraft mass, +1.3 % yr −1 ) (Fig. S6); (ii) total NO x emissions grew by +4.5 % yr −1 , which is likely attributable to the higher combustion pressure and temperature in more fuel-efficient engines (Kyprianidis and Dahlquist, 2017; Freeman et al, 2018); (iii) the mean nvPM EI n increased by +0.5 % yr −1 ; and (iv) the contrail cirrus net RF showed significant inter-annual variability (up to ±19 % relative to the mean, ranging between 204 and 280 mW m −2 ), consistent with Wilhelm et al (2021), indicating a stronger dependence on meteorology than the total flight distance (Fig. S12).…”
Section: Multi-year Statisticssupporting
confidence: 56%
“…When the model is evaluated using forecast meteorology, the output can be interpreted as a forecast of expected contrail climate forcing for a specific aircraft flying nominal cruise conditions through a grid cell. While output accuracy is currently limited by known challenges in forecasting upper tropospheric humidity [25,26,28], this output effectively emulates the size and distribution of contrail forecast data for the purposes of quantifying cost and avoidance feasibility.…”
Section: Avoidance Regionsmentioning
confidence: 99%
“…While further studies are required to assess the accuracy and efficacy of contrail forecast models [26][27][28], this study seeks to understand the costs and feasibility of contrail avoidance from an operations perspective, assuming accurate avoidance regions are available. This paper utilizes a prototypical contrail forecast model based on the CoCiP model publicly available through the Contrails API [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Computational models have collated legacy and new understanding of contrails, allowing the simulation of their lifecycle. Error bars given in IPCC charts are comprised of natural variability, model inadequacy, and scenario uncertainty [5]. Considering weather variability alone (a subset of natural variability), Monte Carlo runs conducted on a simple contrail model in [5] show large scatter of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Error bars given in IPCC charts are comprised of natural variability, model inadequacy, and scenario uncertainty [5]. Considering weather variability alone (a subset of natural variability), Monte Carlo runs conducted on a simple contrail model in [5] show large scatter of the results. It is concluded that uncertainty levels are unlikely to ever reach values considered acceptable [5].…”
Section: Introductionmentioning
confidence: 99%